Performance and Emissions of a Turbocharging Diesel Engine Using B10 and Supercharging Syngas on Dual Fuel - Sutheerasak, Ekkachai; Ruengphrathuengsuka, Wirogana; Sanitjai, Surachai (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 3 (2019): July-September 2019, 2019)
In Thailand, the ministry of energy needs to increase the use of renewable energies, especially biodiesel and syngas, more than 25%. However, blending biodiesel more than 10% provided lower engine performance significantly. Therefore, this research aims to present about the investigating performance and emissions of a turbocharging diesel engine using the diesel blended to 10% biodiesel (B10) compared with the use of B10 and syngas on dual fuel. Syngas was generated from a downdraft gasifier by using the charcoal, and it was increased the gas flow rate from 76 to 125 lpm by using a supercharger. Results of using B10 compared with diesel show that the fuel properties of B10 were similar to diesel. Engine performance was decreased slightly, but emissions, such as carbon monoxide, hydrocarbon, and black smoke, were also reduced. Results of engine test using the dual fuel between B10 and increasing syngas quantity (B10+SG) indicate that the use of B10+SG at 85 lpm had similar engine performance to using diesel only. Use of B10+SG at 125 lpm was the best because of higher engine performance and more fuel saving as compared with using B10 and diesel only. On the other hand, the use of B10+SG compared with using both oils only show that various emissions were enormously increased while the syngas quantity was increased to 125 lpm. Keywords: B10, syngas, diesel engine, performance, emissions